TEKNIK BELAH KOLONI DAN MODEL STUP UNTUK PENINGKATAN PRODUKTIVITAS LEBAH TANPA SENGAT - Prastiyo, Andi; Muchtar, Andi Asikin; Nuraeni, Sitti; Rahman, Abd.; Latif, Nurfadilah (LPPM Universitas Bina Bangsa, 2025)
The productivity of stingless bees in Indonesia is hindered by farmers' limited knowledge of proper beekeeping techniques, such as colony splitting and hive optimization. This community service program aimed to improve productivity by training farmers on effective colony splitting and introducing optimal hive models. Activities included problem identification, material delivery, demonstrations, hands-on practice, and evaluation. The hive model used had dimensions of 15x15x20 cm for the lower section and 30x30x8 cm for the upper topping, supporting colony sustainability. Results showed 70% of farmers had 1-10 years of beekeeping experience, with 60% owning 1-20 colonies. Colony splitting was the main method for increasing colonies (40%), while 70% of farmers harvested honey 1-2 times per year. Training evaluations highlighted improved farmer understanding of colony splitting and hive use, offering practical solutions to enhance stingless bee productivity through better beekeeping practices